The Present State and Future Perspectives of Cardiac Regenerative Therapy Using Human Pluripotent Stem Cells - Soma, Yusuke; Morita, Yuika; Kishino, Yoshikazu; Kanazawa, Hideaki; Fukuda, Keiichi; Tohyama, Shugo (Frontiers in Cardiovascular Medicine, 2021)
The number of patients with heart failure (HF) is increasing with aging in our society worldwide. Patients with HF who are resistant to medication and device therapy are candidates for heart transplantation (HT). However, the shortage of donor hearts is a serious issue. As an alternative to HT, cardiac regenerative therapy using human pluripotent stem cells (hPSCs), such as human embryonic stem cells and induced pluripotent stem cells, is expected to be realized. Differentiation of hPSCs into cardiomyocytes (CMs) is facilitated by mimicking normal heart development. To prevent tumorigenesis after transplantation, it is important to eliminate non-CMs, including residual hPSCs, and select only CMs. Among many CM selection systems, metabolic selection based on the differences in metabolism between CMs and non-CMs is favorable in terms of cost and efficacy. Large-scale culture systems have been developed because a large number of hPSC-derived CMs (hPSC-CMs) are required for transplantation in clinical settings. In large animal models, hPSC-CMs transplanted into the myocardium improved cardiac function in a myocardial infarction model. Although post-transplantation arrhythmia and immune rejection remain problems, their mechanisms and solutions are under investigation. In this manner, the problems of cardiac regenerative therapy are being solved individually. Thus, cardiac regenerative therapy with hPSC-CMs is expected to become a safe and effective treatment for HF in the near future. In this review, we describe previous studies related to hPSC-CMs and discuss the future perspectives of cardiac regenerative therapy using hPSC-CMs.